EFFECT OF PLASMA NITRIDED-LAYER MICROSTRUCTURE OF 42CrMo STEEL ON IMPACT FRETTING WEAR PROPERTY - ZHANG ZhiXing; REN YanPing; GAO Heng; LI ZhongWen; LU JinSheng; CAI ZhenBing; ZHU MinHao (Jixie qiangdu)
Plasma nitriding of the quenching and tempering 42 CrMo steel was carried out at 530 ℃ using two different N2-H2 atmospheres: 3% N2 and 80% N2,which prepared two types of samples with different compound layers,ε + γ’ compound-phase andγ’ single-phase,respectively. Impact wear tests were performed using the impact wear test rig controlled by kinetic energy. The effect of nitrided-layer microstructure control on impact fretting wear property of 42 CrMo steel was studied. The results show that the impact wear properties of 42 CrMo steel can be improved by plasma nitriding,the hardness of the plasma nitrided samples are higher than that of the 42 CrMo steel samples,and the peak impact force and energy absorption rate of the plasma nitrided samples were lower. Compared with the γ’ single-phase sample,the ε + γ’ compound phase sample show better impact wear properties due to its higher hardness and better impact dynamic response. The impact wear mechanism of 42 CrMo steel is plastic deformation,peeling wear and oxidative wear. The impact wear mechanism of nitrided samples is fatigue spalling,slight abrasive wear and oxidative wear. Plasma nitriding significantly reduces spalling and oxidation of 42 CrMo steel during impact wear,and the degree of oxidation of the wear scars on γ’ single-phase samples was slighter than that of ε + γ’ composite phase samples.